Peningkatan Kemampuan Memahami Isi Bacaan melalui Kegiatan Membaca Kritis: Enhancing Reading Comprehension through Critical Reading Activities - Sutiono Sutiono (Fenomena, 2008)
A common phenomenon in Indonesia is that people enjoy reading but only to pass the time, without making a genuine effort to comprehend information deeply. The main problem in teaching reading at schools is students’ low ability to understand reading content due to inappropriate approaches. This study aims to describe teachers’ efforts to improve reading comprehension through critical reading activities among tenth-grade students at SMA Negeri 1 Kencong, Jember. This classroom action research was conducted in three cycles, involving teachers and researchers in planning, action, observation, and reflection. The instruments used included questionnaires, observations, interviews, document analysis, and diaries. The results showed an increase in reading interest from 40% (cycle I) to 92.5% (cycle III), critical reading activities from 47.5% to 92.5%, and reading comprehension ability from 47.5% to 92.5%. The application of critical reading proved effective in enhancing students’ comprehension. It is recommended that teachers consistently apply critical reading techniques in Indonesian language instruction. Fenomena umum di Indonesia adalah masyarakat gemar membaca tetapi hanya untuk mengisi waktu luang, tanpa upaya memahami informasi secara mendalam. Masalah utama dalam pembelajaran membaca di sekolah adalah rendahnya kemampuan siswa memahami isi bacaan karena pendekatan yang kurang tepat. Penelitian ini bertujuan mendeskripsikan upaya guru dalam meningkatkan pemahaman isi bacaan melalui kegiatan membaca kritis pada siswa kelas X SMA Negeri 1 Kencong, Jember. Penelitian tindakan kelas ini dilaksanakan dalam tiga siklus dengan melibatkan guru dan peneliti dalam perencanaan, tindakan, observasi, dan refleksi. Instrumen yang digunakan meliputi angket, observasi, wawancara, analisis dokumen, dan catatan harian. Hasil penelitian menunjukkan peningkatan minat membaca dari 40% (siklus I) menjadi 92,5% (siklus III), aktivitas membaca kritis dari 47,5% menjadi 92,5%, dan kemampuan memahami isi bacaan dari 47,5% menjadi 92,5%. Penerapan membaca kritis terbukti efektif meningkatkan pemahaman siswa. Direkomendasikan agar guru menerapkan teknik membaca kritis secara berkelanjutan dalam pembelajaran bahasa Indonesia.